Keanekaragaman Jenis Bivalvia di Perairan Laut Desa Donggulu Kecamatan Kasimbar Kabupaten Parigi Mautong - Rio Gunawan; Bustamin Bustamin; Masrianih Masrianih; Syech Zainal (Media Eksakta, 2021)
Bivalves are a class within molluscs that includes all shells that have a pair of shells. This study aims to describe the diversity of bivalves in the waters of Donggulu village, Kasimbar district, Parigi Moutong district and the types of bivalves obtained can be used as a learning resource in the form of a pocket book. This research was conducted in Ocean Waters in Donggulu Village, Kasimbar District, Parigi Moutong Regency in February 2020. This type of research is descriptive, sampling using cruising techniques by dividing stations into three stations. The results of the research and identification found 15 types of bivalves, namely Anodonta anatina, Spondylus gaederopus, Macoma balthica, Macoma elimata, Anadara granusa, Anadara gubernaculum, Anadara sativa, Anadara sp, Vasticardium flavum, Donax faba, Hippopus hippopus, Tridacna maxsima, Paphia gallus, Gafrarium sp, and Gafrarium pectinatum. The diversity index obtained is H '= 1.088 which indicates that the bivalve species are at a moderate level. The validation of research results as a learning resource in the form of a pocket book yielded a percentage89.675% which indicates that it is feasible to be used as a learning resource